IMPLEMENTATION OF A GIS-BASED SYSTEM FOR URBAN ELECTROMAGNETIC HAZARD MANAGEMENT (Web of Technology: Multidimensional Research Journal, 2024)
Electromagnetic fields (EMFs) generated by various urban infrastructure systems, such as power lines, telecommunications, and broadcasting stations, can pose potential health risks to the urban population. With the increasing expansion of urban areas and the growing use of electronic devices, the management of electromagnetic hazards becomes a significant concern for public health and safety. Geographic Information Systems (GIS) offer powerful tools for spatially analyzing and managing EMF risks in urban environments. This article discusses the implementation of a GIS-based system for urban electromagnetic hazard management, exploring the integration of EMF data with spatial data, risk mapping, and mitigation strategies.